2021
DOI: 10.1108/er-11-2020-0489
|View full text |Cite
|
Sign up to set email alerts
|

Working with emotions: cultural employee perspectives to service management expectations

Abstract: PurposeDrawing on the emotional labour theory, the purpose of this paper is to explore the effects of cultural orientation on emotion regulation and display processes for service employees.Design/methodology/approachBased on a Nigerian study where literature is scarce, data were gathered from semi-structured interviews conducted with 40 call centre service agents.FindingsThe findings identified three key values around reinforcing social cohesion, anticipated self-curtailment, hierarchy and expressions of servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Demircioglu (2021) investigated the effect of senior management style and leadership on employee job satisfaction in Australia and concluded that top-down management style is negatively associated with employee job satisfaction. Babatunde et al. (2021) studied employee culture and management expectations; the findings identified three key values around reinforcing social cohesion, anticipated self-curtailment, hierarchy and expressions of servility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Demircioglu (2021) investigated the effect of senior management style and leadership on employee job satisfaction in Australia and concluded that top-down management style is negatively associated with employee job satisfaction. Babatunde et al. (2021) studied employee culture and management expectations; the findings identified three key values around reinforcing social cohesion, anticipated self-curtailment, hierarchy and expressions of servility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Demircioglu (2021) investigated the effect of senior management style and leadership on employee job satisfaction in Australia and concluded that top-down management style is negatively associated with employee job satisfaction. Babatunde et al (2021) studied employee culture and management expectations; the findings identified three key values around reinforcing social cohesion, anticipated self-curtailment, hierarchy and expressions of servility. Obeng et al (2021) examined the effects of high-performance work practices on turnover intention through the mediating role of employee morale; the study concluded that training and empowerment had a significant influence on turnover intention.…”
Section: Bij 3010mentioning
confidence: 99%
“…Individuals' emotions, thoughts and actions are largely context-bound and vary with organisational and societal norms (Syed & Ali, 2013). To date, emotional labour has primarily been investigated in North America, Europe and other Western contexts; therefore, the contextual and nuanced nature of emotional labour, particularly in the Asian context, remains underexplored (Babatunde et al, 2021;Bozionelos, 2016;O'Donohoe & Turley, 2006;Syed & Ali, 2013;Syed et al, 2006). To bridge this gap, this study explored how male and female nurses performed and experienced emotional labour in Sri Lanka's public and private hospitals.…”
Section: Emotional Labour Gender and Nursingmentioning
confidence: 99%
“…It is believed the degree of employee engagement depends on how efficiently a team of employees are built and how far each employee and leader can understand each other's emotions. The changing business environment in the global village, EI, is the key problem for managing projects particularly in the IT sector (Babatunde et al, 2021). The lack of adequate professionals in the industry of software development, the vast possibilities they possess or the mismatch in the context of personality that tends to take place are the main reasons why EI has become a necessary component in the team-building process.…”
Section: Introductionmentioning
confidence: 99%